SISTEM MONITORING DAN PENGENDALI SUHU SERTA KELEMBABAN UDARA PADA TANAMAN ANGGREK BERBASIS IOT DENGAN NodeMCU - dani sasmoko; Sumaryanto Sumaryanto; Reni Veliyanti; ARS Wicaksana (Hexagon Jurnal Teknik dan Sains, 2022)
Indonesia is a country that is rich in various kinds of living things, various kinds of flora and fauna that do not exist in other parts of the world in Indonesia. Nearly 30 thousand-50 thousand types of plants live in the archipelago. UPTD Gardens of the Semarang City Agricultural Service is a place for plant cultivation, such as vegetables, fruits and ornamental plants. Especially in the orchid plant section, it focuses more on the cultivation of orchids such as the Moon Orchid (Phalaenopsi), Vanda, Cattleya, Dendrobium, but the Dendrobium Orchid is more of a priority because it is easy to plant and affordable by the community. In this study, the maintenance process using IoT technology is able to support garden supervisors so that plant care can be done from anywhere and anytime. Figure 7 shows information on the temperature and humidity of orchid plants. In addition, there is a button if you want to do watering and turn on the fan to make the temperature and humidity optimal. In Figures 8 and 9 data is obtained from the history of temperature and humidity that has been experienced by orchid plants. So from this research system the garden supervisor is very helpful because the watering process becomes easier and to determine the temperature and humidity values ????no longer use estimates that are sometimes wrong but will already get the amount of the value